Modeling Mud and Sand Transfers Between a Macrotidal Estuary and the Continental Shelf: Influence of the Sediment Transport Parameterization. Issue 4 (14th April 2020) - Diaz, M.; Grasso, F.; Le Hir, P.; Sottolichio, A.; Caillaud, M.; Thouvenin, B.
Abstract: Coastal environments are directly influenced by terrigenous inputs coming from rivers through estuaries. Quantifying the amount of nutrients and contaminants transported by sediments from continental areas to the sea is crucial for marine resources protection. However, the complexity of estuarine dynamics makes it difficult to quantify sediment fluxes from field measurements alone and requires numerical modeling. Thus, using a realistic 3‐D hydrodynamic and sediment transport model, this study aims at evaluating the influence of model empirical parameters on sediment fluxes and estimating uncertainties on mud and sand transfers at a macrotidal estuary mouth. A sensitivity analysis, considering changes in sediment transport parameters, revealed that the system is sensitive not only to settling and erosion parameterizations but also to the spin‐up period and the sediment sliding process. Both estuarine circulation and tidal pumping induce a residual up‐estuary transport, which is balanced by seaward export during spring tides. Although more fine sediments are exported within the surface turbid plume during high river discharge, the net mud transport is directed up‐estuary due to increased baroclinic circulation. Besides, model results highlighted a strong seasonal variability in sediment fluxes with a short and high import during high river flow and a long and weak export during low river flow. Uncertainties associated with the simulated fluxes were about 93% for mud and 51% for noncohesive classes, based on the best performing parameter sets for surface suspended sediment concentrations. These results can be reliably extrapolated to similar macrotidal estuarine systems. Plain Language Summary: Estuaries are transitional zones between terrestrial and marine environments (freshwater vs. saltwater). Because of their potential to transport nutrients and contaminants, quantifying the amount of sediment particles (mud and sand) exchanged at this interfacial area is essential for marine resources protection. Here, we use a realistic numerical model of sediment transport applied to an estuary and its adjacent continental shelf. Some parameters in the model are not well known and require calibration. This study aims at evaluating the impact of various model calibrations on simulated sediment exchanges at the estuary mouth. We found that the simulated sediment behavior is very sensitive to the selected model parameters. The quantity and direction of simulated exchanges are influenced by the parameterization of sediment erosion and settling (i.e., the rate at which particles are suspended and settle out). The dominant physical processes driving these exchanges are strongly influenced by river flow and tide amplitude. Sediment transfers are very intense and directed upstream during a short period in winter and compensated by weak export seaward during a long period in summer. Besides, uncertainties associated with simulated sediment exchanges are about 93% for mud and 51% for sands, which can reliably be applied to similar estuarine systems. Key Points: A 3‐D process‐based model is used to study sediment fluxes sensitivity to sediment transport parameters along an estuary‐shelf system Besides erosion and settling parameterizations, sediment fluxes are notably sensitive to sediment sliding process and spin‐up period For equifinal parameter sets, uncertainties associated with sediment fluxes at the estuary mouth can reach 93% for mud and 51% for sands